Generation of controllable spectrum in multiple positions from speckle patterns. (May 2022) - Li, Haoran; Wu, Xiaoyan; Liu, Guodong; Vinu, R.V.; Wang, Xiaoyan; Chen, Ziyang; Pu, Jixiong
Highlights: Non-dominated sorting genetic algorithm II (NSGA2) with a step-by-step strategy is designed to achieve multiple-position spectrum modulation. Programmable two-position spectrum filter is experimentally implemented, and the spectral width, shape and magnitude of two positions can be flexible adjusted. A comparison between NSGA2 and traditional algorithm is illustrated to demonstrate the superiority of NSGA2. Abstract: Feedback-based wavefront shaping has been proposed to modulate the speckle field generated by coherent light transmitting through scattering media. Different from a monochromatic light, a colorful speckle pattern is generated when polychromatic light transmits through scattering media. Although single-position spectrum modulation has been realized, multiple-position spectrum modulation is a much more complicated problem. Based on non-dominated sorting genetic algorithm II (NSGA2), we design a step-by-step strategy to solve this problem. The results show that modulated spectra in two spatial positions with controllable spectral shape, range and magnitude can be achieved. This research is expected to be applied in the field of adaptive spectral control ranging from advanced spectral filtering to optical fiber dispersion and multi-spectral imaging.